THE PURPOSE OF THIS RESEARCH IS TO EXAMINE EMPIRICALLY THE INFLUENCE OF DEVIDEND PER SHARE (DPS), RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), END RETURN ON ASSET (ROA) TO STOCK PRICE. ( Study Kasus Manufakturing Company, Industrial Sectors and Chemical Sectors in Indonesia Strock Exchange 2013-2016) - Eka Fitria Wulandari; Roni Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRAK The purpose of this research is to examine the influence of Devidend Per Share (DPS), Return On Equity (ROE), Net Profit Margin (NPM), and Return On Asset (ROA) on strock price stock. The sample in this study is a manufacturing company, and industrial sectors and chemil sectors in indonesia strock exchange in 2013-2016. Methods of statistical analysis used multiple regression with SPSS 16.0 for windows.The results show that Devidend Per Share (DPS) not significantly affect the strock price. Return On Equity (ROE) not significantly affect the strock price. Net Profit Margin (NPM) not significantly affect the stock price. Return on asset (ROA) significantly affect the stock price.Keywords : Devidend Per Share (DPS), Return On Equity (ROE), Net Profit Margin (NPM), Return On Asset (ROA), stock price.